Investigation of the initial feasibility of extended mathematics read-alouds used by kindergarten teachers - Powell, Sarah R.; Moore, Clinton E.; Vander Tuin, Mackenna; Fall, Anna-Mari; Roberts, Greg (Frontiers in Education, 2024)
Read-alouds provide teachers with an efficacious method for introducing vocabulary and content to young children. In this study, kindergarten teachers were randomly assigned to implement a mathematics-focused extended read-aloud program called TEMPLE (Teaching Early Math by Providing Language Exploration) with kindergarten children ages 5-6 (19 teachers with 169 children) or to a business-as-usual (BaU) condition (17 teachers and 146 children). With TEMPLE, teachers used read-alouds with storybooks to introduce mathematics vocabulary and content with each read-aloud accompanied by a brief mathematics activity for a period of up to 18 weeks. At posttest, TEMPLE children demonstrated an advantage on two measures of mathematics, but the difference between TEMPLE and BaU children was not significant. In an analysis related to implementation fidelity, we identified a positive and significant association between the number of book readings that TEMPLE teachers reported and scores on one of the mathematics measures. Limited implementation of the program may have led to these results.